PENGARUH LITERASI KEUANGAN, PENETAPAN SKALA PRIORITAS, DAN PENGGUNAAN DIGITAL PAYMENT TERHADAP KEMAMPUAN MANAJEMEN KEUANGAN PRIBADI MAHASISWA PRODI PENDIDIKAN EKONOMI - Yuli Anti, Ria; Bagus Efendi, Farid; Dian Purnama Windrayadi, Yosia (STKIP MAJENANG, 2025)
The convenience of digital payments and the advancement of financial technology may influence on students' purchasing decisions, making sound financial management and financial literacy crucial. The objective of this study is to examine how students in the Economics Education Study Program's personal financial management abilities are impacted by financial literacy, priority scale setting, and digital payment usage. A quantitative associative research strategy is used, with 64 students serving as a sample from a population of 173 pupils chosen by purposive sampling. Questionnaires were used to gather data, and SPSS version 23 was used for analysis. The findings indicate that priority scales and financial literacy have a beneficial impact on personal financial management, while digital payment have no effect. However, concurrently, these three independent variables exert influence on students’ personal financial management.